1995
DOI: 10.1159/000139340
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Dependent and Endothelium-lndependent Vasodilation in Hyperthyroid and Hypothyroid Rats

Abstract: The effects of hyper- and hypothyroidism on the vasorelaxing responses to acetylcholine (ACh), sodium nitroprusside (NP), and CaCl2 were investigated in aortic strips and isolated perfused kidneys. The renal vascular reactivity to ACh and NP was increased in hyperthyroid rats, whereas the concentration-response curve to ACh in hypothyroid rats was flattened. In the renal vasculature from hypothyroid rats, NP produced a dual response: vasoconstriction at low doses and vasodilation at medium to high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 16 publications
4
28
1
Order By: Relevance
“…These data are consistent with the increased and decreased responsiveness to acetylcholine, the endothelium-dependent vasodilator, in perfused kidneys and isolated aortas from hyperthyroid and hypothyroid rats respectively (5). Our data in the hypothyroid group contrast with the increased staining of endothelial NOS using immunohistochemical techniques in the aortic endothelium of hypothyroid rats (30).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These data are consistent with the increased and decreased responsiveness to acetylcholine, the endothelium-dependent vasodilator, in perfused kidneys and isolated aortas from hyperthyroid and hypothyroid rats respectively (5). Our data in the hypothyroid group contrast with the increased staining of endothelial NOS using immunohistochemical techniques in the aortic endothelium of hypothyroid rats (30).…”
Section: Discussionsupporting
confidence: 88%
“…Hyperthyroidism manifests a hyperdynamic circulation with increased cardiac output, increased heart rate and decreased peripheral resistance, whereas the hypothyroid state is associated with low cardiac output, bradycardia and raised peripheral resistance (2 -4). Hyperthyroidism increases the responsiveness of resistance vessels to the endothelium-dependent vasodilator, acetylcholine, whereas methimazole-induced hypothyroidism attenuates the endothelium-dependent response (5). Thyroid dysfunctions also affect cardiac and renal weight as well as renal sodium handling (2,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Further, these findings are consistent with earlier findings concerning vascular function. We (Delp et al 1995, McAllister et al 2000 and others (Vargas et al 1995) have found endothelium-dependent dilation of rat vasculature to be blunted in hypothyroidism; conversely, we (McAllister et al 1998(McAllister et al , 2000 and others (Scivoletto et al 1986, Vargas et al 1995, Honda et al 2000 have observed augmented endothelium-dependent vasodilation in the hyperthyroid state. Since a primary mediator of endothelium-dependent dilation in vasculature of the rat is NO (Delp et al 1993), our findings collectively suggest that alterations in endothelium-dependent vasodilation with changes in thyroid status are, in part, accounted for by an altered capacity for NO formation.…”
Section: Capacity For No Formationmentioning
confidence: 48%
“…Endothelium-independent vasodilation has generally been reported to be normal in both the hypothyroid (Delp et al 1995, McAllister et al 2000 and hyperthyroid states (McAllister et al 1998(McAllister et al , 2000, although exceptions have been reported (Vargas et al 1995, Honda et al 2000. Collectively, these findings suggest that thyroid status primarily affects the vascular endothelium.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation